Grounded theory in genetic counseling research: an interpretive perspective. - Grubs RE; Piantanida M (Journal of Genetic Counseling, 2010)
As qualitative inquiry has gained wider acceptance in genetic counseling research, it has become increasingly important for researchers and those who evaluate their work to recognize the diversity of methods that fall under this broad umbrella. Some of these methods adhere to the traditional conventions of scientific research (e.g., objectivity, reliability, validity, replicability, causality and generalizability). When such studies are evaluated by reviewers who are well versed in scientific methods, the rigor of the study may be readily apparent. However, when researchers are using methods that do not conform to traditional scientific conventions, the distinction between well conducted and poorly conducted studies may become more difficult to discern. This article focuses on grounded theory because it is a widely used qualitative method. We highlight key components of this method in order to contrast conventions that fall within a scientific paradigm to those that fall within an interpretivist paradigm. The intent is to illustrate how the conventions within these two different paradigms yield different types of knowledge claims -- both of which can advance genetic counseling theory and practice.